Effect of Organic Copper, Zinc and Manganese Supplementation on Growth, Immunity and Hatchability of Egg in Japanese Quail (Coturnix coturnix japonica) - Satapathy, A. K.; Das, S. K.; Sethy, K.; Swain, R. K; Mishra, S. K.; Behera, K.; Pati, S. (Indian Journal of Animal Nutrition, 2020)
To assess the effect of organic copper (Cu), zinc (Zn) and manganese (Mn) supplementation on immunity and hatchability,  405 six week old Japanese quails (Coturnix coturnix japonica) were randomly distributed into  nine dietary treatment groups and the experiment continued till  the period up to 13th week. The dietary treatments were T0:100 % inorganic minerals (Cu, Zn and Mn); T1: 100 % organic minerals (Cu, Zn and Mn); T2:  100 % inorganic Zn and Cu with 100 % organic Mn; T3: 100 % inorganic Zn and Cu with 50 % organic Mn and 50% inorganic Mn; T4 :  100 % inorganic Zn and Mn with 100 % organic Cu; T5 : 100 % inorganic Zn and Mn with 50 % organic Cu and 50% inorganic Cu; T6 : 100 % inorganic Mn and Cu with 100 % organic Zn; T7 : 100 % inorganic Mn and Cu with 50 % organic Zn and 50% inorganic Zn; T8 : 50 % organic Zn, Cu and Mn with 50 % inorganic Zn, Cu and Mn.  Basal diets were supplemented with Cu, Zn and Mn at the levels of 5, 25 and 60 ppm, respectively. Results revealed that supplementation of organic Cu, Zn and Mn had no effect on growth rate, blood chemistry and weight of lymphoid organs, but the hatchability of eggs and cutaneous basophil hypersensitivity response were significantly (P